Information System for Selection of Production Line for Plastic Item Injection Machine Number A36 Using Priority Scheduling Method - Dani Chairudin, Muchamad; Ginting, Novita Br.; Fajri, Hersanto (Universitas Nusantara PGRI Kediri, 2020)
A PT. Astra Components Indonesia manufactures injection plastic goods to be sent to customers, in the production process the machines used are capable of producing several types of injection plastic goods, so that products can be provided regularly and there is a process of changing products or better known as the Dandory process. Found an obstacle that is an error in determining the order of dandory for production. Consequently, the condition of goods in the warehouse is irregular. It is detrimental to the company with the time, material and labour that has been expended for production so that an Information System is needed to determine the priority schedule for the replacement of injection plastic goods in this study taking the case at machine number A36. The system development uses the Waterfall method; the system description will be described by the Unified Modeling Language Modeling (UML) method. Data collection is done by observing directly observing production activities in the company as well as interviews with relevant parties, and for solving problems, the system will be assisted by Priority Scheduling method. The results of the research get an information system that will provide recommendations for items that will first be produced appropriately.